Adult-Onset Ornithine Transcarbamylase Deficiency in a 51-Year-Old Man Who Presented With Fatal Hyperammonemic Encephalopathy - Bun Sheng; Ka Fai Yim; Tiffany Yan Lok Lam; Candace Yim Chan; Hencher Han Chih Lee (Annals of Internal Medicine: Clinical Cases)
Typical male patients with ornithine transcarbamylase deficiency present in their early years with lethargy, seizure, and coma from hyperammonemia. An adult-onset phenotype, with sudden severe hyperammonemia emerging in otherwise-healthy men, has been increasingly recognized. We describe a characteristic clinical course in a 51-year-old Chinese man who developed fatal hyperammonemia after receiving systemic corticosteroid for Bell's palsy. The genetic sequencing detected a novel missense variant NM_000531.6:c.642C>A (p.His214Gln) in the OTC gene. Inherited urea cycle disorders should be suspected in unexplained hyperammonemia at all ages with aggressive treatment initiated promptly before a diagnosis is confirmed.